2019
DOI: 10.17576/jskm-2019-1702-11
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychology of Epilepsy in Malaysia: A Narrative Review

Abstract: The aim of this study is to describe the development of neuropsychological research among epilepsy patients in Malaysia so far, the current trend and the focus of future research endeavour. The research in epilepsy grows concurrently with the interest in the field of neuropsychology in Malaysia. Beginning with the presurgical evaluation of epilepsy patients as part of the epilepsy protocols, research areas expanded further into neuropsychological profiling. The current trend in Malaysia is determining the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In general, mean parental reported QOL score was higher than that of child self-report. 12 It is important to keep parental anxiety in our mind that can affect QOL scores. Williams et al reported that over-anxious parents are more likely to perceive higher risk for their children and may misinterpret information about their child's condition 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, mean parental reported QOL score was higher than that of child self-report. 12 It is important to keep parental anxiety in our mind that can affect QOL scores. Williams et al reported that over-anxious parents are more likely to perceive higher risk for their children and may misinterpret information about their child's condition 13 .…”
Section: Discussionmentioning
confidence: 99%